How does Economic Integration Change Personal Income Taxation? Evidence from a new Index of Potential Labor Mobility - Benjamin Protte (University of Mannheim, Department of Economics, 2012)
In this paper, I estimate the effect of increasing labor mobility on personal income tax schedules. I combine rich data on effective personal income tax levels in a panel of OECD countries for the period 1986-2005 with a new Index of Potential Labor Mobility. This index allows to tackle issues of reverse causality and potentially confounding effects from strategic competition. Estimates show that increasing labor mobility accounts for a considerable part of lower tax burdens. Furthermore, the reduction is found to be constant across brackets of taxable income.
urn:nbn:de:bsz:180-madoc-325903
Keywords: H24; F22; J61; 330; Personal Income; Taxation; Economic Integration; Labor Mobility